POPULATION GROWTH AND REGIONAL STABILITY IN CENTRAL ASIA - Ibroxim Ibraximov Baxtiyor o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Population Growth and Regional Stability in Central Asia Central Asia is one the few regions in the world where the population continuous to grow rapidly. While many countries in Western Europe and North America are dealing with aging populations and shrinking workforces, but Central Asian states are experiencing the opposite trend. Between 1950 and 2023, the region’s population grew from 17.5 million to 80.8 million (UNFPA EECA, 2025). Uzbekistan is the most populated country in the region, with 37.4 million people in 2024, and about half of its population is under the age of 30 (Krzyżanowska, 2025; UNFPA EECA, 2025). This paper asks: How does rapid population growth influence regional stability and labor migration in Uzbekistan? The main argument is that population growth creates a short-term opportunity for economic development, known as the “demographic dividend”. But it also increases labor migration, puts pressure on cities and infrastructure, and may lead to long-term economic tension if the government does not act. The key challenge for Uzbekistan is to use this opportunity while it lasts. The most obvious impact of the growing population in Uzbekistan is the rise in labor migration. Each year, an estimated 780,000 people enter the workforce, while the domestic economy cannot generate sufficient employment for each (UNFPA EECA, 2025). In consequence, many seek employment abroad; an estimated 2-8 million Uzbek citizens are currently working outside their country, the highest amount among the countries of Central Asia (Marat, 2009). The sum of funds transferred by migrant workers in 2024 reached 4.8 billion, equals to 14% of the country’s GDP (World Bank, 2025). Whereas without remittances, the poverty rate would rise from 9.6 to 16.8% (World Bank, 2025). Thus, a substantial portion of Uzbek households receive the means to meet basic economic needs from the Russian, South Korean or Kazakh labor markets rather than from domestic economic development efforts by the state.